Política de inovação na indústria eletrônica: uma análise nacional do Programa Prime e uma aplicação para o APL de TIC de Campina Grande(PB) - Cardoso, Altamar Alencar (2013)
This study aimed to analyze the evolution of innovation policy and national PRIME Program and its local application in APL ICT Campina Grande. The methodology consists of : the application of the type and arrangement for local production and innovation systems as Cavalcanti Filho (2013 ) to characterize the cluster of ICT in Campina Grande , in the application of the systemic model of public policy analysis in conjunction with the cycle model public policy as Street (2009 ) to analyze the process of formation and implementation of the PRIME program . For data acquisition was used desk research , questionnaires and interviews . There was an evolution in the design of industrial policy and innovation in response to economic developments , in particular the process of globalization . Regarding the PRIME program , he presented barriers to implementation derived from inconsistencies in the design phase of the program , yet its goal was achieved in 85 % of participating companies in the case of PaqTc . A significant effect was the achievement instill in companies the importance of developing management skills and marketing , both considered weak in APL ICT companies Campina Grande. These new companies with business profile differentiated from standard corporate APL is an important variant of the arrangement and result in increased sales , one of the bottlenecks found by the analysis of APL . Therefore, the PRIME program was an important mechanism of variation within APL ICT Campina Grande ( PB ) .